The effect of Coptotermes kalshoveni Kemner towards Melaleuca Cajuputi (Gelam) Wood and Acacia Mangium Wood - Nor Anis Adila Mohamad (2016)
Melaleuca cajuputi and Acacia mangium wood have many beneﬁcial uses suchas in building construction, furniture and can be planted at wide sites. Coptotermes kalshoveni Kemner was known as a key genus that caused destructions in wooden structures and trees. This study was conducted:- i) to compare the durability between M. cajuputi and A. mangium woods, ii) to identify the effect of drying and non-drying methods on woods towards termites attack and iii) to determine the preference of termites attack towards raw and treated woods of M. cajuputi and A. mangium using choice and no-choice test. Seasoning treatment (oven drying) was applied on the woods to reduce the moisture content. The treatment was conducted in oven at 105°C for six hours. t-Test was done to identify the signiﬁcant difference in mean of weight loss between raw and treated woods of M. cajuputi and A. mangium in choice and no-choice test. The percentage weight loss of raw and treated woods of M. cajuputi are 9.03% and 0.73% respectively which are lower compared to the raw and treated woods of A. mangium (13.22% and 2.14% respectively). Therefore, M. cajuputi wood has higher durability compared to A. mangium wood. This is because previous study showed that the cajuput oil content in M. cajuputi tree was used as insect repellent and thus, increase the resistance of the wood against pests. The duration for the day where the mortality rate of termite to reached 100% for raw wood of M. cajuputi and A.mangium (seven days) is longer compared to the treated wood (ﬁve days). Thus, the termite attack increase towards the raw wood of M. cajuputi and A. mangium compared to the treated wood. The termites that feed on raw wood of M. cajuputi able to survive more days because the raw wood contain more moisture contain in cellulose compared to treated wood. Based on the visual rating analysis in choice test, the preference of C. kalshoveni attack towards raw wood of M. cajuputi (day three) and A. mangium (day one) is higher compared to treated wood of M. cajuputi (day four) and A. mangium (day two). In choice test, the termites avoid the treated wood when preferred raw wood is available. The usage of effective wood treatment method can reduce the amount of chemicals and preservatives needed to protect the wood and also can increase the longevity of the wood.